AN INTRODUCTORY APPROACH TO PAIN MANAGEMENT THROUGH AYURVEDA WITH BRIEF HOLISTIC REVIEW (AYUSHDHARA, 2018)
The whole world is fighting with pain whatever may be its source or origin. Pain is a protective body mechanism, which alerts the person about the harmful condition or experience that occurs in the body .In Ayurveda, Vata Dosha is the root cause of all types of pain (Shoola) - “Vatat rute Nasti Ruja” as mentioned by Acharya Sushruta. The concept of pain in Ayurveda is based on the fundamental theories of Tridoshas, Triguna, Srotas and Ojas, but it has also certain relations with the Karma of previous birth as depicted by Maharishi Charaka as “Karmaja Roga” . The Ayurvedic texts describes a wide range of pain; Shoola (piercing pain), being most prominent form, Dank (bursting), Vedana (unbearable sensation), Dagdha (burning pain), Chosa (sucking pain), Nirmathan (churning like), Shastraviddh (cutting like), Spandana (vibration) are some of other expressions. Associated Doshas with the Vata can alter the type and intensity of the pain as dull aching and from sharp neuralgic pain to burning pain in Kapha and Pitta associated Vata Dosha respectively. The hindrance in Vata Dosha flow leads to the pain. In modern medicine, Pain is the most common symptoms of inflammatory process, like wise use of NSAIDs is associated  with risk of fatal gastrointestinal bleeding, increase  in stomach acid, reduce the stomach normal protective mucus layer, cause damage to the kidneys in people over 60; those with high blood pressure, heart disease, or pre-existing kidney diseases. All Ayurvedic treatments and therapies involve bio purification of body channels as well as immune stabilization and management of psyche, strengthen and enhance the body own healing process and donot have adverse effects, if given in proper dose according to the fundamental principles of Ayurveda.